2015
DOI: 10.1016/bs.irn.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Genetic Evidence for GIRK Channels in the CNS

Abstract: G protein-coupled inwardly rectifying potassium (GIRK) channels are widely expressed throughout the brain and mediate the inhibitory effects of many neurotransmitters. As a result, these channels are important for normal CNS function and have also been implicated in Down syndrome, Parkinson’s disease, psychiatric disorders, epilepsy, and drug addiction. Knockout mouse models have provided extensive insight into the significance of GIRK channels under these conditions. This review examines the behavioral and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 136 publications
(192 reference statements)
0
19
0
Order By: Relevance
“…Originally implicated for their role in epilepsy (Maljevic & Lerche, 2014; Smets et al, 2015), studies show that calcium-activated (K Ca ), voltage-dependent (K V ), and G protein-coupled inwardly-rectifying (K ir ) K + channels are targets for both acute and chronic effects of ethanol (Hopf et al, 2011; Mayfield, Blednov, & Harris, 2015; Mulholland, 2012; Mulholland, Hopf, et al, 2009). Additionally, preclinical studies have demonstrated that chronic ethanol reduces the function and trafficking of K Ca 2 ( Kcnn ), K V 4.2 ( Kcnd2 ), and K V 7.2 ( Kcnq2 ) channels in the nucleus accumbens (NAc) and hippocampus (Hopf et al, 2010; McGuier et al, 2015; Mulholland, Spencer, Hu, Kroener, & Chandler, 2015; Padula et al, 2015; Spencer, Mulholland, & Chandler, In Press), and pharmacologically enhancing K Ca 2 and K V 7 channel function attenuated voluntary drinking in rodents (Hopf et al, 2011; Knapp, O’Malley, Datta, & Ciraulo, 2014; McGuier et al, 2015; Padula et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Originally implicated for their role in epilepsy (Maljevic & Lerche, 2014; Smets et al, 2015), studies show that calcium-activated (K Ca ), voltage-dependent (K V ), and G protein-coupled inwardly-rectifying (K ir ) K + channels are targets for both acute and chronic effects of ethanol (Hopf et al, 2011; Mayfield, Blednov, & Harris, 2015; Mulholland, 2012; Mulholland, Hopf, et al, 2009). Additionally, preclinical studies have demonstrated that chronic ethanol reduces the function and trafficking of K Ca 2 ( Kcnn ), K V 4.2 ( Kcnd2 ), and K V 7.2 ( Kcnq2 ) channels in the nucleus accumbens (NAc) and hippocampus (Hopf et al, 2010; McGuier et al, 2015; Mulholland, Spencer, Hu, Kroener, & Chandler, 2015; Padula et al, 2015; Spencer, Mulholland, & Chandler, In Press), and pharmacologically enhancing K Ca 2 and K V 7 channel function attenuated voluntary drinking in rodents (Hopf et al, 2011; Knapp, O’Malley, Datta, & Ciraulo, 2014; McGuier et al, 2015; Padula et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…G protein–gated inwardly rectifying potassium (GIRK or Kir3) channels are expressed in various regions of the brain, where they control the resting membrane potential and excitability of neurons ( Lüscher and Slesinger, 2010 ). Mouse and human molecular genetic studies have indicated a role for GIRK channels in a variety of human disorders, including addiction, alcoholism, Down’s syndrome, and depression (for a review, see Mayfield et al, 2015 ). Similar to other inwardly rectifying potassium channels, activation of GIRK channels hyperpolarizes the membrane potential, reducing neuronal excitability.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic evidence from mouse models has provided extensive insight into the significance of GIRK channels in drug addiction, and their role in responses to ethanol and other drugs of abuse is reviewed in (Bodhinathan & Slesinger, 2014) and (Mayfield, Blednov, & Harris, 2015). …”
Section: Ion Channelsmentioning
confidence: 99%